Pengaruh Pembangunan Infrastruktur Ekonomi Terhadap Pertumbuhan Ekonomi Inklusif Di Sumatra Barat - Alius, Aditya Nugraha; Anis, Ali (Universitas Negeri Padang, 2024)
This research aims to determine the influence of economic infrastructure on inclusive economic growth in West Sumatra from 2014 to 2021. This type of research is quantitative. The object of this research was carried out in all regencies/cities in West Sumatra for the period 2014 to 2021. The type of data used was secondary data that researchers obtained from the West Sumatra Central Bureau of Statistics (BPS). The data analysis method used is panel data regression analysis, with the Chow test, Hausman test and hypothesis test (R2 test, F test and t test), the panel data regression estimation model used is the Fixed Effect Model, data processing uses the E-program Views 12. The results of this research show that together the infrastructure variables electricity, water, roads and communication technology have a significant effect on the level of inclusive economic growth in West Sumatra. Partially: (1) electricity infrastructure has a positive but not significant effect on the level of inclusive economic growth. (2) water infrastructure has a positive and significant effect on the level of inclusive economic growth. (3) road infrastructure has an insignificant positive effect on the level of inclusive economic growth. (4) communications technology infrastructure has a positive and significant effect on the level of inclusive economic growth.